Comparative Evaluation of Implant-Protected Occlusion in Partially Edentulous Fixed Restoration Using Qualitative and Quantitative Assessment – A Prospective Clinical Trial - Ramesh Chowdhary; S Bukkapatnam (Indian Journal of Dental Research)
Objectives: To compare and evaluate the occlusal variability/discrepancy recorded using qualitative (articulating paper) and quantitative (T-scan) techniques in partially edentulous implant-supported restorations. Materials and Methods: A total of 20 patients in the age group of 25–61 yrs participated in this study. All the patients had more than one tooth replaced with implant-supported prosthesis. After three months of restoration, occlusion reevaluated was carried out using qualitative (articulating paper) and quantitative (T-scan). T-scan data were used to measure implant occlusion time, occlusion time, and the relative occlusal force (ROFs) on implant prosthesis. And the data were statistically evaluated. Results: The T-scan values showed high points on the implants in most of the patients, which could not be evaluated by that of articulating paper outcomes. Conclusion: The occlusal harmony achieved from using qualitative analysis of articulating paper was not supported by the finding of the quantitative analysis (T-scan). Also the T-scan provided the time interval of occlusion of the implant-supported restorations, which would help in better defining the implant-protected occlusal. Clinical Relevance: The T-scan occlusal analysis system provides ROF and time intervals of occlusal contact. This allows accurate occlusal equilibration of implant-supported restoration according to implant protected occlusal concept.